2005
DOI: 10.1097/01.idc.0000179881.82808.fe
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Diagnostic Criteria of Brucellosis in an Endemic Area in Egypt

Abstract: A case-control study was conducted during the year 2003 in Tanta Fever Hospital within an endemic area for brucellosis (Br) in Egypt. One hundred forty-nine cases of Br and 298 patients with other infectious diseases were consecutively enrolled. Risk factors of Br (adjusted odds ratio) were having sheep (6.2 folds), high-risk occupation such as farmers and butchers (4.5 folds), having an aborted animal (3.5 folds), and increasing age (1.04 fold per year). Previous admission into a fever hospital within a yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…Yet such results are in agreement with of our previous study (El Sherbini et al, 2005), although they disagree with those of Almuneef et al (2004), Al-Shamahy et al (2000) and Al-Talafhah et al (2003), indicating that risk factors for brucellosis must be assessed in each community to identify the most appropriate control and prevention measures.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Yet such results are in agreement with of our previous study (El Sherbini et al, 2005), although they disagree with those of Almuneef et al (2004), Al-Shamahy et al (2000) and Al-Talafhah et al (2003), indicating that risk factors for brucellosis must be assessed in each community to identify the most appropriate control and prevention measures.…”
Section: Discussionsupporting
confidence: 69%
“…The association between keeping sheep and human brucellosis has also been found as the major risk factor for this zoonosis in our case-control study (El Sherbini et al, 2005). Several reports claim sheep to have the highest proportion of brucellosis infection among livestock (Almuneef et al, 2004;Al-Shamahy et al, 2000).…”
Section: Discussionmentioning
confidence: 70%
“…16,17 As compared to other Middle Eastern countries, this prevalence is significantly lower than that reported in Saudi Arabia 5 and similar to that reported in Iraq, 12 Israel, 7 and Egypt. 19 In this study, the seroprevalence of childhood brucellosis was found to be significantly higher in Mafraq and Ma'an governorates compared to the other governorates. Studies on the epidemiology of brucellosis in small ruminants and camels in Jordan revealed similar findings for these two governorates.…”
Section: Discussionmentioning
confidence: 52%
“…That large endemic for brucellosis. The eradication policy needs ruminants had a significantly higher seroprevalence to be reinforced with measures that will guard against than the small ruminants disagrees with the findings of all risk factors for brucellosis at all levels and farmers El Sherbini et al [30] who found sheep had the highest need to be more compensated for the total cost of prevalence among livestock in a study in Egypt but animals lost or provided with full insurance schemes. agrees with the findings of Omer et al [31] in Eritrea, Small ruminants seem to be more susceptible to who found husbandry systems have effect on the brucellosis than the large ruminants but this needs prevalence of brucellosis and large ruminants had further investigation and increasing the number of higher prevalence than small ruminants.…”
Section: Discussionmentioning
confidence: 95%